Pemeriksaan Imunologi Terhadap Kadar Hormon Thyroid Stimulating Hormone (TSH) Pada Pasien Gangguan Tiroid Di RSUD Panembahan Senopati Periode 2020-2022 - Rifka Aulia Astuti; Farida Noor Irfani (Lembaga Pengembangan Kinerja Dosen, 2024)
Thyroid disorders are conditions of abnormalities in thyroid gland. According to function, thyroid disorders are divided into three, hyperthyroidism, hypothyroidism and euthyroidism. To detect thyroid disorders, can use laboratory test examination of TSH (Thyroid Stimulating Hormone) hormone. The aim is to determine the description of TSH levels checked periodically in patients with thyroid disorders using immunological methods. Research method is a case series method or case-by-case using secondary data from TSH hormone examination results in 2020-2022. The results were from 93 respondents based on age showed that 20-30 years old 11.8%, 31-40 years old 26.9%, 41-50 years old 26.9% and 51-60 years old 34.4%. Based on gender, 20.4% were male and 79.6% were female. Then we looked at changes in TSH hormone in patients with thyroid disorders by randomization 10 respondents. It was found that the changes were caused by consumption of anti-thyroid drugs, Thiamazole, Propranolol, Thyrozol, Propylthiouracil, Levothyroxine. Respondents with thyroid disorders were mostly found in 51-60 years and were female. There are changes in TSH hormone levels in patients with thyroid disorders were anti-thyroid drugs. The immunological method used ECLIA (Electrochemiluminescence Immunoassay) method. Factors that influence examination are the condition of sample and patient.